Alignment of process compliance and monitoring requirements in dynamic business collaborations. Issue 6 (3rd July 2017) - Comuzzi, Marco
ABSTRACT: Dynamic business collaborations are intrinsically characterised by change because processes can be distributed or outsourced and partners may be substituted by new ones with enhanced or different capabilities. In this context, compliance requirements management becomes particularly challenging. Partners in a collaboration may join and leave dynamically and tasks over which compliance requirements are specified may be consequently distributed or delegated to new partners. This article considers the issue of aligning compliance requirements in a dynamic business collaboration with the monitoring requirements induced on the collaborating partners when change occurs. We first provide a conceptual model of business collaborations and their compliance requirements, introducing the concept of monitoring capabilities induced by compliance requirements. Then, we present a set of mechanisms to ensure consistency between monitoring and compliance requirements in the presence of change, e.g. when tasks are delegated or backsourced in-house. We also discuss a set of metrics to evaluate the status of a collaboration in respect of compliance monitorability. Finally, we discuss a prototype implementation of our framework.